Comments on "computation of the gravity field and its gradient". (September 2017) - Zhang, Dailei; Huang, Danian
Highlights: Locating errors and inaccurate descriptions in their context, equations and codes. Giving an effective method to calculate gravity gradient of the vertical cylinder. Providing correct and comprehensive MATLAB codes for the model calculation. Discussing the method used and how to improve the work in the future.